Carbon secrets: Quantifying biomass and carbon stock potential of Sal (Shorea robusta Gaertn.) in a community forest of Makawanpur, Central Nepal - Gautam, Raj Kumar; Dhakal, Debendra Prasad; Bhattarai, Prakash (FORESTRY: Journal of Institute of Forestry, Nepal, 2025)
In Nepal, carbon sequestration potential of Sal (Shorea robusta) in community forests (CFs) is understudied. This study assessed aboveground biomass (AGB) and belowground biomass (BGB) and estimated the carbon stock potential of Sal trees in Neureni–Chisapani CF, Makawanpur district, Central Nepal. Data were collected from 16 circular plots of 250 m2 each, established across four blocks. All Sal trees with DBH ≥ 5 cm were measured. The AGB was calculated by using allometric equations and BGB by root–shoot ratios, and the total biomass was converted to carbon stock using the standard carbon fraction. Environmental factors, including altitude, soil pH and rock cover, were recorded to find their relationships with the carbon stock. The forest stored an average of 248.97 t/ha of AGB, 64.72 t/ha of BGB, 313.69 t/ha of total biomass and 146.96 t/ha of carbon. A total of 13.87 m2/ha of basal area was calculated. Block-level carbon ranged from 137.79 to 158.12 t/ha, though ANOVA showed no significant difference (p > 0.05). The carbon stock strongly correlated with DBH, height and basal area; however, Generalized Linear Model showed unimodal and curvilinear relationships with altitude, soil pH and rock cover. Thus, these results confirm CFs as good carbon reservoirs, which helps to develop climate change mitigation strategies and sustainable forest management policies.